Drugs for the Treatment of Chronic Hand Eczema: Successes and Key Challenges [Corrigendum] - Dubin C; Del Duca E; Guttman-Yassky E (Dove Medical Press, 2021)
Dubin C, Del Duca E, Guttman-Yassky E. Ther Clin Risk Manag. 2020;16:1319– 1332. The authors have advised the drug, ARQ-252, was misnamed in the paper as roflumilast (which is called ARQ-151 and ARQ-154 by the manufacturer). The drug named ARQ-252 by the manufacturer should instead be classified as a JAK1 inhibitor in the paper. On page 1320, CHE Treatment Paradigm section, 1st paragraph, “There are also ongoing studies with phosphodiesterase type 4 inhibitors (PDE4) and inhibitors of highly inflammatory chemokines CCL2 and CCL5 for the treatment of mild to moderate CHE. 1,35– 38” should read “There are also ongoing studies with topical JAK1 inhibitors and inhibitors of highly inflammatory chemokines CCL2 and CCL5 for the treatment of mild to moderate CHE. 1,35– 38”. On page 1322, Table 1, Agent and Target/Mechanism columns, “Roflumilast (ARQ-252)” should read “ARQ-252” and “PDE4” should read “JAK1”. On page 1323, before Roflumilast section, new section added for ARQ-252:ARQ-252Another topical JAK inhibitor is currently under investigation for the treatment of CHE. ARQ-252, a topical JAK1 inhibitor, is under clinical evaluation in a phase 1/2b randomized parallel assignment trial involving 223 patients with chronic hand eczema. 37,90 On page 1323, Roflumilast section now reads “Roflumilast is a high potency selective inhibitor of the receptor for PDE4, which functions by degrading cyclic adenosine monophosphate (cAMP). 89 Blocking the PDE-4 receptor allows cAMP to signal the transcription of immune function genes such as anti-inflammatory IL-10, while simultaneously reducing the production of inflammatory cytokines such as TNFα and IFN γ, which have been identified as possibly involved in CHE. 15,91-93 Roflumilast has been investigated as a topical therapeutic for AD, 89 and though there are no current trials, it remains a possible therapeutic option for CHE in the future. The authors apologize for this error.Read the original article